ANALISIS KADAR LOGAM BERAT TEMBAGA (Cu) DAN KADMIUM (Cd) PADA IKAN KAKAP (Lates calcalifer) ASAL TAKALAR SECARA SPEKTROFOTOMETRI SERAPAN ATOM - A. Muflihunna (Fakultas Farmasi UMI, 2012)
The analysis of Cuprum (Cu) and Cadmium (Cd) content had been done of Kakap fish (Lates calcalifer) in Tope Jawa and Satanga Island. This research aim to analyse and determine the quantity of Cuprum (Cu) and Cadnium (Cd) of Kakap fish (Lates calcalifer) by Atomic Absorption Spectrophotometry (AAS). This research was done by dry destruction both types of the metal, then the result of destruction dissolved in acid. Its result then analysed qualitative by specific reaktan and analysed quantitative by Atomic Absorption Spectrophotometry of wavelength 324,8 nm for the Cuprum and 228,8 nm for the Cadmium. The result of research obtained that Kakap fish in Tope Jawa and Satanga Island contain the metal of Cuprum (Cu) and Cadmium (Cd) but not exceed the boundary of rate maximum specified by DITJEN POMKey Word: Cuprum (Cu), Cadmium (Cd), Kakap fish and AAS